PENGARUH DAN PEMANFAATAN BEASISWA PROGRAM INDONESIA PINTAR (PIP) TERHADAP HASIL BELAJAR SISWA SMKN 1 TILATANG KAMANG - 2118-2123, Ismail (Universitas Negeri Padang, 2018)
Abstract-This research is motivated by the condition of education in Indonesia deteriorating. The high cost of education generating the dropout rate, especially the higher the middle level. The PIP program is rolled out to overcoming the problem. The purpose of this research is to knowing the utilization of busary PIP used by students and the there is or there no of influence PIP program to student outcomes learning SMK N1 Tilatang Kamang. Type of research used is research expost facto with descriptive research method. The population of students of SMKN 1 Tilatang Kamang received PIP is counted to 120 students. The sample of research is 55 students by using technique of Propotional Random Sampling. The research instrument used is a questionnaire with Likert scale. The research trial was conducted on 30 students recipient of PIP in SMKN 1 Tilatang Kamang. Based on the results of research that has been done, it can be concluded that the bursary received by students used to buy school clothes and school supplies, transprotation fees and pocket money, as well as for the cost prakerin is exploited goodness by students. Student learning outcomes between before with after receiving PIP there is an increase and there is also a decrease. A total of 31 students (56.36%) of the 55 students who received the PIP improved learning outcomes, and as many as 24 students (43.64%) of 55 students experienced a decrease in learning outcomes. Key Word: PIP bursary, utilization, study result